Developing self-development skills in autistic children at Sidikalang State SLB - Kontesalonika Br Sinulingga; Rahmahtrisilvia Rahmahtrisilvia; Annisa Amalia; Rahmi Mufa Rananta; Rizka Nurida Siregar; Septian Hadinata (Lembaga Riset Mutiara Akbar, 2026)
This study aims to describe the implementation of the self-development program for autistic children at Sidikalang State Special School (SLB Negeri), including the teaching strategies applied, challenges encountered, and efforts undertaken to address those challenges. A descriptive qualitative approach was employed, with teachers and autistic students serving as research subjects. Data were collected through observations and in-depth interviews and analyzed using descriptive techniques. The findings reveal that the self-development program is systematically integrated into scheduled learning activities to foster students’ independence in daily living skills. Teachers implement various strategies, including structured teaching, visual media, modeling, repetitive practice, positive reinforcement, and collaboration with parents. The implementation process, however, faces several challenges, such as difficulties in understanding instructions, limited attention span, repetitive behaviors, low motivation, and inadequate facilities. To overcome these barriers, teachers simplify instructions, provide direct demonstrations, utilize engaging visual media, consistently reinforce positive behaviors, and strengthen communication with parents. The study concludes that a structured and consistent self-development program supported by appropriate instructional strategies and active parental involvement can effectively enhance the independence of autistic children in performing daily activities.